Digital Impact on Beauty Salons: E-Service Quality, E-Promotion, Customer Satisfaction and Purchase Decisions - Wahyuni, Pita Hadi Sri; Hidayati , Nur; Asiyah , Siti (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to prove the direct and indirect influence of e-service quality, e-promotion and purchase decisions on customer satisfaction. Design/methodology/approach: The sampling technique used was accidental sampling with a total of 96 respondents. Meanwhile, the data analysis tool uses Structural Equation Modelling (SEM) with the PLS version 4.0 application. Research Findings: Based on the results of data analysis, it shows that e-service quality and purchase decisions have no effect on customer satisfaction, while e-service quality and e-promotion have an effect on purchase decisions, e-promotion has an effect on customer satisfaction, then purchase decisions have not been able to mediate the influence of e-service quality and e-promotion on customer satisfaction. Theoretical Contribution/Originality: This study increases understanding of the role of using beauty services via electronic platforms. Consumers experience secondary services that are not directly related to primary services, providing an integrative view of the value of satisfaction and purchasing decisions. This study shows the feasibility of applying advanced PLS techniques to investigate consumer behaviour, especially in the field of implementing e-service quality and e-promotion. Implications for consumer satisfaction and purchasing decisions are also derived from these findings. Keywords: E-Service Quality; E-Promotion; SEM-PLS; Customer Satisfaction; Purchase Decisions